Immediate primary anastomosis for isolated oesophageal atresia: A single-centre experience - Ibrahim Uygun; Hikmet Zeytun; Selcuk Otcu (African Journal of Paediatric Surgery, 2015)
Background: Isolated oesophageal atresia without tracheo-oesophageal fistula represents a major challenge for most paediatric surgeons. Here, we present our experience with six neonates with isolated oesophageal atresia who successfully underwent immediate primary anastomosis using multiple Livaditis circular myotomy. Materials and Methods: All six neonates were gross type A isolated oesophageal atresia (6%), from among 102 neonates with oesophageal atresia, treated between January 2009 and December 2013. Five neonates were female; one was male. The mean birth weight was 2300 (range 1700-3100) g. Results: All six neonates successfully underwent immediate primary anastomosis using multiple myotomies (mean 3; range 2-4) within 10 (median 3) days after birth. The gap under traction ranged from 6 to 7 cm. One neonate died of a major cardiac anomaly. Another neonate was lost to follow-up after being well for 3 months. Three anastomotic strictures were treated with balloon dilatation, and four anastomotic leaks were treated conservatively. The mean duration of follow-up was 33 months. Conclusions: To treat isolated oesophageal atresia, an immediate primary anastomosis can be achieved using multiple myotomies. Although, this approach is associated with high complication rates, as are other similar approaches, these complications can be overcome.